IMPROVE-IT: what have we learned?. (July 2016) - Banach, Maciej; Nikolic, Dragana; Rizzo, Manfredi; Toth, Peter P.
Abstract : Purpose of review: Recent studies and dyslipidemia treatment guidelines indicate that combination lipid-lowering therapy is frequently needed and its use has increased in recent years. Ezetimibe and simvastatin as a fixed dose is an efficacious treatment choice based on positive results of the recent IMProved Reduction of Outcomes: Vytorin Efficacy International Trial (IMPROVE-IT). In this review, we discuss recent controversies surrounding ezetimibe and provide clinical perspective on the results of the IMPROVE-IT study. Recent findings: IMPROVE-IT is the first trial that demonstrates a significant clinical benefit of a nonstatin hypolipidemic agent (ezetimibe) used in combination with statin (simvastatin) therapy in patients who have experienced an acute coronary syndrome. For almost a decade, the use of ezetimibe was limited by a relative lack of definitive evidence. However, the most recent Plaque Regression With Cholesterol Absorption Inhibitor or Synthesis Inhibitor Evaluated by Intravascular Ultrasound study showed greater coronary plaque regression by statin/ezetimibe combination compared with statin monotherapy. The results of the IMPROVE-IT trial are fostering new debate about the value of adjunctive low-density lipoprotein cholesterol lowering over and above a statin. Summary: Ezetimibe/simvastatin combination, either as a single pill or as the combined use of the individual compounds, represents a well-tolerated and efficacious choice for dyslipidemia treatment in high-risk subjects, including patients with diabetes. Limited additional risk for adverse events compared with simvastatin monotherapy is observed, and an individualized, patient-centered approach to therapy is recommended.